Influence of thermal stress during in vitro maturation on the developmental competence of oocytes and embryos and the expression of Sirtuins in cumulus oocyte complexes in cattle - Ralf Pöhland; Mirela Brochado Souza-Cáceres; Tirtha Kumar Datta; Jens Vanselow; Wilian Aparecido Leite da Silva; Christopher Junior Tavares Cardoso; Fabiana de Andrade Melo Sterza (Semina: Ciências Agrárias)
Sirtuins are of central importance in many cellular functions and promote cell survival under stress. However, little information is available regarding the relationship between sirtuins and female reproductive biology, especially in response to thermal stress. This study investigated the influence of moderately high (40°C) and low (37°C) thermal stress during in vitro maturation on the development competence of bovine oocytes and embryos. The expression and abundance of sirtuins and other proteins involved in stress response were also studied. The cumulus-oocyte complexes (COCs) of Simmental (Bos taurus) cows underwent in vitro maturation (IVM) at different temperatures (37°C, 38.5°C and 40°C). Before maturation, the oocytes were stained with Brilliant Cresyl Blue (BCB) and categorized as labeled (BCB+) or unlabeled (BCB-). Embryo production was analyzed at the different IVM temperatures. Polar body extrusion was evaluated following IVM, and the mRNA and protein abundance of sirtuins and P53 in oocytes and cumulus cells were analyzed. The differing temperatures during IVM did not significantly alter polar body extrusion and cleavage rates; however, significant differences in blastocyst production were observed. COCs matured at 38.5°C (control) had the highest blastocyst rate, in contrast to those matured at 37°C (33.2%) and 40°C (21.5%). In all groups, the blastocyst rates were higher for BCB+ oocytes than for BCB- oocytes. In BCB+ oocytes, the expression of SIRT1, SIRT2, SIRT3, and SIRT5 genes was higher after maturation than that before maturation and in most of the cases, the expression was higher when IVM was performed at 38.5°C. In the cumulus cells of BCB+ COCs, only SIRT2 remained unaffected by the maturation temperature. In summary, the temperature change of ±1.5°C for 24 h during bovine oocyte maturation impaired in vitro embryo development. This lead to several cellular biochemical alterations in oocytes and granulosa cells from COCs with higher developmental competence (BCB+). Thus, SIRT1 is important for in vitro embryonic development and may protect against cold and heat stress.